Prevalence of shoulder morbidity after treatment for breast cancer in South Africa - Kramer, Nicole (Institute of Infectious Disease and Molecular Medicine, 2018)
Introduction: Breast cancer is the most frequently diagnosed cancer and leading cause of cancer death among women and represents a considerable public health burden in South Africa and other low-middle income countries. Breast cancer management comprises single or combination treatment including surgery, radiotherapy and chemotherapy. Short and long-term complications of these treatments include shoulder morbidities such as pain, decreased range of motion, tightness, weakness, pain, numbness and lymphoedema, and may be present for up to 6 years post-surgery. An understanding of baseline demographic and clinical risk factors can guide rehabilitation and management strategies for high risk patients. Materials and Methods: This study was a cross-sectional analysis of the prevalence of shoulder pain and dysfunction in women attending their post-treatment annual follow up visit for unilateral breast carcinoma. The aim of this study was to quantify the burden of shoulder pain and disability in a tertiary academic hospital in Cape Town, South Africa, and identify potential risk factors for the development of shoulder morbidity. The primary objective of this study was to determine the prevalence of shoulder morbidity and the secondary objective was to evaluate associations between shoulder morbidity and risk factors such as treatment protocol or baseline demographics. Results: The majority of patients were of mixed ancestry, had their left side affected, received ALND and had undergone Modified Radical Mastectomy. The mean age was 60 years with a mean follow-up since surgery of 6 years. Three-quarters of patients reported a presence of pain or disability; 9% experienced severe pain and disability. Multivariable ordinal logistic regression analysis identified race, side, axillary surgery, chemotherapy and age as significant predictors of pain, and chemotherapy a significant predictor of disability. Discussion: The substantial burden of shoulder morbidity in this population represents a significant public health burden. The use of identified clinical and demographic characteristics may guide in the development of survivorship programmes incorporating surveillance and management of these high risk patients.